BOOK REVIEW OF GAYLE FORMAN’S I WAS HERE - Roefmelinda, Aldeana (LANTERN (Journal on English Language, Culture and Literature), 2016)
It is often done as a result of, for examples, despair, depression, mental disorders, bipolar disorder, alcohol dependence or drug abuse. The factors that also causes suicide include financial difficulties or problems in interpersonal relationship. Efforts to prevent suicide among other things are by limiting access to firearms, caring for mental illness and drug abuse, as well as improving economic conditions.